2020
DOI: 10.1111/ane.13248
|View full text |Cite
|
Sign up to set email alerts
|

The evidence for switching dibenzazepines in people with epilepsy

Abstract: The tolerability of AED regimes is crucial to treatment adherence, as non-concordance is a major cause of breakthrough seizures for people on long-term AEDs. 1 Now that there is significant "real-world" experience alongside trial data with a newer AED, eslicarbazepine acetate, we review the available efficacy and tolerability data, particularly in comparison with standard AEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The overnight transition between oxcarbazepine and eslicarbazepine acetate (or vice versa) in a 1:1 ratio is generally well tolerated [4][5][6][7]. The overnight transition between carbamazepine and eslicarbazepine acetate (or vice versa) in a ratio of 1:1.3-1.5 is reasonable [4]. In case of need, these drugs can be interchanged instantly considering the above-mentioned ratios.…”
Section: Eslicarbazepine Acetate/oxcarbazepine/ Carbamazepinementioning
confidence: 99%
“…The overnight transition between oxcarbazepine and eslicarbazepine acetate (or vice versa) in a 1:1 ratio is generally well tolerated [4][5][6][7]. The overnight transition between carbamazepine and eslicarbazepine acetate (or vice versa) in a ratio of 1:1.3-1.5 is reasonable [4]. In case of need, these drugs can be interchanged instantly considering the above-mentioned ratios.…”
Section: Eslicarbazepine Acetate/oxcarbazepine/ Carbamazepinementioning
confidence: 99%
“…Only SANAD I has studied large scale head to head ASM montherapies; the study reported a non-significant advantage of CBZ over OXC [2], ESL was not included in the study. There is however, some emerging, low grade evidence confirming efficacy of the newer dibenzazepines in individuals switched from CBZ to either of the newer agents, as well as some support in switching from OXC to ESL [33,34].…”
Section: Do the New Asms Work As Well As Cbz?mentioning
confidence: 99%
“…There are several reports indicating clinical risks associated with a substitution from the original anti-epileptic to a generic (and vice versa) or from one generic to another, such as: adverse events, breakthrough seizures, emergency department visits and hospitalizations [3,[8][9][10][11][12]. In addition to a potential deterioration of treatment effectiveness, a pharmacy switch may challenge a patient's compliance and lead to modifications in his/her anti-epileptic treatment scheme [6,13].…”
Section: Introductionmentioning
confidence: 99%